2021
DOI: 10.3390/cancers13061256
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Efficacy of PD-L1 Targeted Alpha-Particle Therapy in a Human Melanoma Xenograft Model

Abstract: PD-L1 (programmed death-ligand 1, B7-H1, CD274), the ligand for PD-1 inhibitory receptor, is expressed on various tumors, and its expression is correlated with a poor prognosis in melanoma. Anti-PD-L1 mAbs have been developed along with anti-CTLA-4 and anti-PD-1 antibodies for immune checkpoint inhibitor (ICI) therapy, and anti-PD-1 mAbs are now used as first line treatment in melanoma. However, many patients do not respond to ICI therapies, and therefore new treatment alternatives should be developed. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…As shown on Figure 2a and 2b , and in accordance with our previous reports 14 , the adoptive transfer of PD-1 KO T-lymphocytes (yellow dotted lines) but not that of WT T-lymphocytes (gray dotted lines), significantly delayed tumor growth compared to the control group (black lines) ( p < .0001). In addition, confirming our recently published results, 19 anti-PD-L1 TAT also significantly delayed tumor growth (red dotted lines, p < .0001). Monotherapies with either PD-1 KO T-cells or TAT both exhibited a better anti-tumor efficacy than monotherapy with WT T-cells ( p = .003 and p = .027, respectively).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As shown on Figure 2a and 2b , and in accordance with our previous reports 14 , the adoptive transfer of PD-1 KO T-lymphocytes (yellow dotted lines) but not that of WT T-lymphocytes (gray dotted lines), significantly delayed tumor growth compared to the control group (black lines) ( p < .0001). In addition, confirming our recently published results, 19 anti-PD-L1 TAT also significantly delayed tumor growth (red dotted lines, p < .0001). Monotherapies with either PD-1 KO T-cells or TAT both exhibited a better anti-tumor efficacy than monotherapy with WT T-cells ( p = .003 and p = .027, respectively).…”
Section: Resultssupporting
confidence: 91%
“…injection, some hematological toxicity related to ionizing radiation is expected. As already observed in our previous study 19 , platelet counts were significantly decreased in all groups treated with TAT alone or TAT in combination with melanoma-specific T-cells. More surprisingly, we also observed some toxicity on RBC in all the groups but the one treated with the combination of TAT and WT melanoma-specific T-cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…33 In our research, we also assessed the prognostic ability of the HOXA family in cervical cancer Increasing evidence suggests that immune cells play critical roles in carcinogenesis and progression, and a proper proportion of T-cell subsets could contribute to the long-term clinical benefits of anticancer treatments. 36,37 In this study, we applied the online tool ImmuCellAI, a highly accurate method of estimating the abundance of immune cells. 14 Our results showed that under the significantly gands, PD-L1 and PD-L2.…”
Section: Discussionmentioning
confidence: 99%
“…Further work in preclinical models confirmed in vivo stability of 213 Bi-RIC highlighted by a higher amount of activity measured in the blood pool and no specific uptake in kidneys as expected for free bismuth [ 169 ]. Thereafter, a wide range 213 Bi-RIC was developed with most often mAb as targeting agent [ 170 , 171 ], even if antibody fragments [ 172 ] or peptides [ 173 ] were also used. Besides, given that 225 Ac and 213 Bi have common physico-chemical properties, many radioimmunoconjugates were first developed with 213 Bi before transposition to 225 Ac.…”
Section: Bismuth-213mentioning
confidence: 99%